Key Challenges in the Pre-Contract for Building Information Modelling (BIM) Project - ZULFAUZI, NURDINA SARAH; Che Haron, Roziha; MASROM, MD ASRUL NASID (Research in Management of Technology and Business, 2025)
The Malaysian construction industry is undergoing digital transformation throught the Construction 4.0 Strategic Plan (2021-2025), with Building Information Modelling (BIM) playing a key role in enhancing project efficiency. BIM is a technology that enables the creation, communication and analysis of digital models through a construction project’s lifecycle. The pre-construction stage, which includes design, cost estimation, cost planning, and tender preparation, is critical to project success but often encounters data interoperability issues and communication breakdowns, leading to delays and cost overruns. Despite BIM’s potential to improve collaboration, streamline processes, and enhance decision-making, its application remains limited due to reliance on traditional methods. Therefore, this research aims to examine BIM application during the pre-construction stage, identify key challenges and propose strategies for its effective implementation. A mixed-method approach was employed, utilizing questionnaire surveys and interviews for data collection. The findings reveal that the high implementation cost is a significant barrier, limiting its widespread implementation. By addressing these issues, the Malaysian construction industry can accelerate its digital transformation, improving efficiency, collaboration, and competitiveness.